2018
DOI: 10.21767/2380-7245.100179
|View full text |Cite
|
Sign up to set email alerts
|

Approach To Dorsal Nasal Sinus: A Rare Case Report

Abstract: Congenital midline dorsal nasal sinus is a rare clinical presentation in our day today clinical practice. Complete surgical excision can cure the patient. We must be careful while taking decision regarding its surgical management as it may have an intracranial extension and neurosurgical consultation and craniotomy may be required. Here we are discussing our case with the comprehensive approach and review of available literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Phalen, et al found that in about 20% of their cases, preoperative imaging was not consistent with intraoperative findings, and they used MB to delineate the extent of dermoid cyst [6]. Verma and Saha used MB to facilitate dissection of the dermoid sinus [7,8]. Histological examination of frozen sections of the tissue from base of track to detect dermal elements, is another method to determine completeness of resection [9].…”
Section: Discussionmentioning
confidence: 99%
“…Phalen, et al found that in about 20% of their cases, preoperative imaging was not consistent with intraoperative findings, and they used MB to delineate the extent of dermoid cyst [6]. Verma and Saha used MB to facilitate dissection of the dermoid sinus [7,8]. Histological examination of frozen sections of the tissue from base of track to detect dermal elements, is another method to determine completeness of resection [9].…”
Section: Discussionmentioning
confidence: 99%